Práticas translíngues na comunicação de aprendizes de português como língua estrangeira - Milozo, Giovana Nicolini (Universidade Federal de São Carlos, 2019)
This research aims at analyzing and describing communicative practices of four Hispanic learners and one Italian learner, in a Portuguese course offered by a public university in the state of São Paulo, under the Translanguaging perspective. According to Bakhtin (GARCÍA and WEI, 2014), language arises from speaker’s actions, which are endowed with perspectives and ideological position, with impossible neutrality. We intended to understand linguistic performance of those learners beyond linguistic forms and structures. The research questions arose from issues about teaching and learning Portuguese as foreign language, considering “Portuñol” as a stigma, with characteristics of Portuguese and Spanish languages. Translanguaging perspective was chosen by observing that linguistic repertoire of bilingual or multilingual speaker is dynamic and undone. In addition, individual’s linguistic choices are based on adaptive needs to monolingual contexts (GARCÍA et al., 2017). In that perspective, language is understood as a social and cultural practice discursively oriented, with codes and multissemiotic resources and symbolic systems. Those all elements are used by individuals to construct a reality as they are able to conceive (ROCHA e MACIEL, 2015). Described as qualitative interpretative, this research presents characteristics of ethnographic research. Moreover, its methodology consists of data generation and collection in classroom context, and an activity was proposed in order to generate data. The objective of that activity was promoting opportunities to learners to use Portuguese language and to have cultural exchanges. The learners made presentations which aimed to present characteristics of Brazil and of their country. Those presentations were recorded in audio. Subsequently, we proposed individual meetings so that students were able to listen to and reflect on their oral productions. Those meetings were recorded as well. The results were categorized in linguistic and cultural perceptions of him/herself. The linguistic perception reveals a structural perspective about language and student’s conceptions about “error”. The second one reveals student’s perceptions about themselves, including social representations, affective issues and spontaneity in speaking, as well as individual characteristics. All those elements influence, in a particular way, the performance of each student, framing their linguistic repertoire and revealing that his/her biography trajectory is fundamental for the process of speaking foreign languages. We conclude that changing perspectives is important for the area of teaching and learning foreign languages, having the learner as the focus of learning instead of language forms and structures exclusively. In other words, we must prioritize the individual performance, whose linguistic repertoire can be the basis for learning several “named languages”.
Keywords: Ensino e aprendizagem; Português Língua Estrangeira (PLE); Translinguagem; Teaching and learning; Portuguese as foreign language (PFL); Translanguaging; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA